Transfer of Micro‐LEDs with Roll‐Based Direct Overlay Alignment for Manufacturing Transparent Displays - Sung‐Uk Yoon; Yun Hwangbo; Bongkyun Jang; Hyeon‐Don Kim; Jae‐Hyun Kim (Advanced Electronic Materials, 2024)
Abstract Transparent displays are crucial for various applications, particularly for their potential use as windows in future self‐driving cars. These displays require high transparency, low power consumption, and high mechanical reliability. Micro‐LEDs have emerged as ideal devices for the transparent displays. Efficient mass‐production processes are essential for the commercialization of transparent micro‐LED displays. This study presents roll‐based mass transfer to enhance the productivity of transparent micro‐LED displays. Roll transfer processes traditionally face resolution challenges in alignment repeatability and positional errors in both the transverse direction (TD) and machine direction (MD). This study proposes a roll‐to‐plate (R2P) transfer process with overlay alignment to improve the repeatability precision of the alignment. Detailed experimental analyses address positional errors in the TD and MD, attributed to initial contact errors and linear velocity asynchrony, respectively. The results demonstrate successful micro‐LED transfer onto a transparent circuit board (TCB) with a maximum positional error of 3.2 µm and a 99.75% yield. The resulting micro‐LED display achieves a transparency of 72.5% with 68 pixels per inch. This study overcomes the alignment challenges in the R2P process and contributes to the commercialization of transparent micro‐LED displays. It is expected to positively impact the manufacturing of transparent applications that involve rolling processes.